STRATEGIES FOR MOTIVATING AND RETAINING HUMAN RESOURCES IN DENTISTRY - Iulian Costin Lupu; Norina Consuela Forna; Elena-Raluca Baciu; Dana Gabriela Budală; Silviu Cătălin Tibeică; Odette Elena Luca (Romanian Journal of Oral Rehabilitation, 2024)
The motivation and retention of dental staff are important aspects for the success of a dental office or clinic. In an environment where competition is increasing, maintaining, and motivating a united and professionally trained team is essential for the quality of services provided, the patient experience, cost reduction and the promotion of a healthy organizational culture. Investing in employees and creating a stimulating and rewarding work environment can have a significant impact on the long-term success, economic and organizational stability of dental practices. Due to these aspects, strategies must be found and applied to help better motivation and long-term stability of the team.